PENGARUH AIDA (ATTENTION, INTEREST, DESIRE, ACTION) DALAM IKLAN MEDIA SOSIAL INSTAGRAM TERHADAP MINAT MENABUNG NASABAH DI BANK SYARIAH MANDIRI - Muhammad Rafi; Zulfison Zulfison (Journal of Accounting, Management and Islamic Economics, 2023)
Sharia banking in Indonesia has good development potential and one way that can be pursued is to provide information to the public through advertisements related to Islamic banking products. In order to increase interest in saving effectively and efficiently, a concept of AIDA (Attention, Interest, Desire, Action) is needed and social media Instagram as an advertising medium. Therefore, it is necessary to test how much influence AIDA has on the interest in saving. The data collection technique used a questionnaire with a sample of 119 respondents who have become Bank Syariah Mandiri customers and the data analysis used was multiple regression analysis. The results of this study are attention has a significant positive effect on interest in saving, interest has a significant positive effect on interest in saving, desire has a significant positive effect on interest in saving, action has a significant positive effect on interest in saving and AIDA has a significant positive effect on interest in saving.